EFEKTIVITAS PELAYANAN KARTU TANDA PENDUDUK DI KECAMATAN JEBRES KOTA SURAKARTA - Neri Budiarto Mia; Suwardi, Sri Riris Sugiyarti (Solidaritas, 2017)
EFEKTIVITAS PELAYANAN KARTU TANDA PENDUDUK DI KECAMATAN JEBRES KOTA SURAKARTAOleh :Neri Budiarto Mia, Dr.Drs, Suwardi, M.Si., Dra. Sri Riris Sugiyarti, M.Si. The purpose of this research is to know the effectiveness of the service of the identity card (KTP) in Subdistrict Jebres, Surakarta which refers to the 10 dimensions of quality improvement services according to Vincent and other ' (1997:2).The effectiveness showed in the perception of the user/community service with service providers in other words, If there are explosives in an understanding between what is done by the officer/service providers, with the results are perceived by the user/community service, then the service can be said to be effective. The effectiveness of the Ministry can be seen from the performance of the service providers that already produce good results, and the service quality perceived by users of the service.This research uses descriptive quantitative methods. Sampling techniques using incidental sampling, the sample consists of 50 service users/community service/provider and 6 officers. Data collection techniques in the study of using koesioner. The analysis used is servqual (sevice quality) with how to compare between the perception of the users with the perception of the service provider then there is a Gap, the less the service gap between the perceptions of users and service providers the effective services.The results of the ten indicators of the quality of service, timeliness of service have the score Gap (34.6) entered on the classification of